2018
DOI: 10.1016/j.ihj.2017.09.009
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of serum blood urea nitrogen, creatinine and electrolytes in the diagnosis and mortality risk assessment of patients with acute coronary syndrome

Abstract: In addition to cardiac enzymes, K along with BUN and Cr may serve as important aid in diagnosis of ACS. BUN and Cr may also serve as important tools in mortality-risk assessment of ACS patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 25 publications
1
5
0
Order By: Relevance
“…The markers uric acid, homocysteine, hemoglobin, urea, and creatinine were associated with a higher 10year risk for MI, which agrees with the literature [23][24][25][26]. Also, the increase in WC, WHR, ApoB, and ApoB/A1 ratio was associated with a higher 10-year risk of CKD.…”
Section: Discussionsupporting
confidence: 90%
“…The markers uric acid, homocysteine, hemoglobin, urea, and creatinine were associated with a higher 10year risk for MI, which agrees with the literature [23][24][25][26]. Also, the increase in WC, WHR, ApoB, and ApoB/A1 ratio was associated with a higher 10-year risk of CKD.…”
Section: Discussionsupporting
confidence: 90%
“…Patients with elevated BUN levels on admission are several times more likely to die from CVD events. BUN is a relatively common routine test that can effectively mark high-risk patients with acute coronary syndrome (ACS) for close monitoring of any adverse vascular events [ 23 ]. Increases in BUN and creatinine are highly prevalent in patients with ACS, with one in three patients having an increased level of either BUN or creatinine.…”
Section: Discussionmentioning
confidence: 99%
“…Ren et al 38 suggested serum AKP may be a potential predictive biomarker. Adam et al 39 found that K along with BUN and creatinine (Cr) haa a strong relationship in diagnosis of ACS, espectially in mortality-risk assessment of ACS patients. High MCHC and MPV levels may be beneficial for ACS 40.…”
Section: Discussionmentioning
confidence: 99%